Introdução ao desenvolvimento de jogos digitais utilizando o motor de jogo UDK - Marques, Gabriel Cavalcanti (2015)
The research addresses the issue of development of digital games using UDK game engine. It is to provide the potential for development of the UDK game engine, addressing the aspects and characteristics of a digital game production and the ontological stages of development as: brainstorming, concept art, three-dimensional modeling and level design. We also intend to produce material for use as a guide in the development of digital games with the UDK game engine. We find our justification in the fact that the UDK is a free game engine widely used for high-quality standard games, but is lacking in specific introductory materials. Theoretically this research is based on the concepts of development addressed by authors such as Rabin (2012; 2013), Novak (2010; 2011), Thorn (2011), among others, adopting methodology directed to the ontological artistic aspects of the development of digital games. Theoretically, this research is based on the concepts of development addressed by authors such as Rabin (2012; 2013), Novak (2010; 2011), Thorn (2011), among others, adopting methodology directed to the ontological artistic aspects of the development of digital games, according to Petry (2003). Focused on the production of a tutorial, the research also aims to create a navigable prototype illustrating how the tutorial material may result in a digital game or inland environment with a high standard of aesthetic experience and quality